Risk measures with applications in finance and economics - Michael McAleer; Wing Keung Wong (MDPI, 2019)
Risk measures play a vital role in many subfields of economics and finance. It has been proposed that risk measures could be analysed in relation to the performance of variables extracted from empirical real-world data. For example, risk measures may help inform effective monetary and fiscal policies and, therefore, the further development of pricing models for financial assets such as equities, bonds, currencies, and derivative securities. A Special Issue of "Risk Measures with Applications in Finance and Economics" will be devoted to advancements in the mathematical and statistical development of risk measures with applications in finance and economics. This Special Issue will bring together the theory, practice and real-world applications of risk measures. This book is a collection of papers published in the Special Issue of "Risk Measures with Applications in Finance and Economics" for Sustainability in 2018.
Keywords: 330